Conditions of the quality of the relation between self-awareness and the means of self-experience. - Gasiul, Henryk (Studia Psychologica: Theoria et praxis, 2003)
The article presents an attempt at the interpretation of the connection between self-awareness and the means of self-experience. The method of assessment focuses on the experienced feelings in relation to the sphere of meaning in fundamental measurement depending on the central structure “self”. Interference in terms of the realization of motives connected with “self”, like for example the aspiration to preservation of positive self-evaluation, appear to constitute the distinct nature of self-experience. Self-awareness developed in the given culture has equal significance. As a result, cultural or motivational conditions are the main subject of the presented analysis – in which is perceived the cause of diverse relationship qualities between self-awareness and the means of self-experience. The author also develops the theme analyzing the type of indicators on which are based the feelings making up the basis of evaluation. The whole analysis aims at the modification of theoretical bases marking out the possible directions of empirical investigations.